ChemInform Abstract: Mesoporous Mixed Oxide Catalysts via Non‐hydrolytic Sol‐gel: A Review. Issue 16 (28th March 2013) - Debecker, Damien P.; Hulea, Vasile; Mutin, P. Hubert
Abstract Review: 200 refs.